Assessment and misassessment of potassium, phosphorus, and protein in the hemodialysis diet. Issue 5 (29th May 2018) - St‐Jules, David E.; Goldfarb, David S.; Pompeii, Mary Lou; Liebman, Scott E.; Sherman, Richard A.
Abstract: Diet is a key determinant of several common and serious disease complications in hemodialysis (HD) patients. The recommended balance and variety of foods in the HD diet is designed to limit high potassium and phosphorus foods while maintaining protein adequacy. In this report, we examine the potassium, phosphorus, and protein content of foods, and identify critical challenges, and potential pitfalls when translating nutrient prescriptions into dietary guidelines. Our findings highlight the importance of individualized counseling based on a comprehensive dietary assessment by trained diet professionals, namely renal dietitians, for managing diet‐related complications in HD patients.